Optical measurement of glutamate in slice preparations of the mouse retina. (December 2018) - Ohkuma, M.; Kaneda, M.; Yoshida, S.; Fukuda, A.; Miyachi, E.
Highlights: We used a new imaging technique to monitor glutamate dynamics in the mouse retina. High K solutions elevated the glutamate signal. Cd 2+ blocked the K-induced elevation of glutamate. Blocking GABA- and glycinergic inputs elevated the glutamate signal. Abstract: Signaling by glutamatergic synapses plays an important role in visual processing in the retina. In this study, we used an enzyme-linked fluorescence assay system to monitor the dynamics of extracellular glutamate in a slice preparation from the mouse retina. High K stimulation induced an elevation of fluorescence in the inner plexiform layer (IPL) of the retina when glutamate transporters were inhibited bydl - threo -β-benzyloxyaspartic acid (TBOA). The high K-induced fluorescence signals in the IPL were inhibited by the calcium channel blocker Cd 2+ . Blockade of GABAergic and glycinergic circuits by picrotoxin and strychnine also elevated the fluorescence signals in the IPL. Thus, the enzyme-linked fluorescence assay system might be useful for monitoring the bulk concentration of extracellular glutamate released by synapses in the inner retina.